Inhibition of androgen receptor promotes CXC-chemokine receptor 7-mediated prostate cancer cell survival - James J. Hoy (Nature Portfolio, 2017)
Abstract The atypical C-X-C chemokine receptor 7 (CXCR7) has been implicated in supporting aggressive cancer phenotypes in several cancers including prostate cancer. However, the mechanisms driving overexpression of this receptor in cancer are poorly understood. This study investigates the role of androgen receptor (AR) in regulating CXCR7. Androgen deprivation or AR inhibition significantly increased CXCR7 expression in androgen-responsive prostate cancer cell lines, which was accompanied by enhanced epidermal growth factor receptor (EGFR)-mediated mitogenic signaling, promoting tumor cell survival through an androgen-independent signaling program. Using multiple approaches we demonstrate that AR directly binds to the CXCR7 promoter, suppressing transcription. Clustered regularly interspaced short palindromic repeats (CRISPR) directed Cas9 nuclease-mediated gene editing of CXCR7 revealed that prostate cancer cells depend on CXCR7 for proliferation, survival and clonogenic potential. Loss of CXCR7 expression by CRISPR-Cas9 gene editing resulted in a halt of cell proliferation, severely impaired EGFR signaling and the onset of cellular senescence. Characterization of a mutated CXCR7-expressing LNCaP cell clone showed altered intracellular signaling and reduced spheroid formation potential. Our results demonstrate that CXCR7 is a potential target for adjuvant therapy in combination with androgen deprivation therapy (ADT) to prevent androgen-independent tumor cell survival.